Application of fuzzy AHP for ranking and selection of alternatives in construction project management - Prascevic, Natasa; Prascevic, Zivojin (Journal of Civil Engineering and Management, 2017)
The construction project management (CPM) is very important and large segment of entire project management (PM). Realisation of construction projects is usually long term process which requests significant financial, material, human and other resources to fulfil contracted obligations and achieve a good quality of works. Therefore, making good decisions with the satisfaction of various criteria is one of the main conditions to achieve planed business objectives and finish the project in contracted time with good quality. This paper proposes a new procedure for determination of the weights of criteria and alternatives in the Fuzzy analytic hierarchy process (FAHP) with trapezoidal fuzzy number using a new method for finding eigenvelues and eigenvectors of the criteria and alternatives, which is based on expected values of the fuzzy numbers and their products. Local and global fuzzy weights of the alternatives are determined using linear programming. In the paper a formula for ranking fuzzy numbers by reduced generalized fuzzy mean is also proposed, since ranking by the coefficient of variation is not always reliable. In the presented case study, applying proposed method, from imprecise input data are obtained enough accurate and useful results for rational ranking of alternatives related to the project realization.